Ecopolitics Podcast, Episode 15: Climate Action in and by Canada: ENGO Voices - Katz-Rosene, Ryan; Andrée, Peter (Université d'Ottawa | University of Ottawa, 2020)
What role do ENGOs play in the Canadian ecopolitical sphere? Catherine Abreu, Executive Director of Climate Action Network Canada, and Colleen Thorpe, Executive Director of Équiterre walk us through the roles their organizations play in fighting for climate policy and shifting cultural norms in Canada. [Produced by Nicole Bedford; Artwork by Adam Gibbard; Transcription by Allison Brown; Additional Resources prepared by Ashley Fearnall].